Fatigue life prediction for a vessel sailing the North Atlantic route - Baxevani, Anastassia; Rychlik, Igor (2007)
A method for calculating the wave load induced fatigue damage accumulated by a vessel sailing along the North Atlantic route (NAr) is presented. This method is based on the Palmgren-Miner additive rule and the rainflow cycle (RFC) count. For simplicity, the load the vessel experiences is assumed to be proportional to the encountered significant wave height process, $H_s$. The asymptotically normal character of the nominal damage is proved and used to derive the probability distribution of the fatigue life prediction. The proposed method improves the already existing ones by making use of the information contained in the variance of the fatigue damage accumulated during the voyages. The method is illustrated through numerical examples.